Digital slurry decorated ceramic tile with decoration durability and preparation method of digital slurry decorated ceramic tile

Through the digital slurry process and multi-stage ball milling process, a thicker decorative layer is formed, which solves the problem of too thin decorative layer of ceramic tiles, enriches the pattern texture and improves the durability of decoration.

CN119350066AActive Publication Date: 2025-01-24GUANGDONG JIA MEI CERAMIC +4
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411486782.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The decorative layer of existing ceramic tiles is too thin, resulting in poor decorative durability and difficult to meet the requirements of public places with large flow of people.

Method used

Using digital slurry process, through a specific slurry formula and multi -stage ball mill process, forming a decorative layer with a thickness of 0.5mm and 1.0mm, combined with the layer of water -based water resistance and protecting the glazed layer, improve the decoration of ceramic tiles durable to durability sex.

Benefits of technology

The richness and fineness of ceramic tile patterns is realized, and the wear resistance and durability of the decorative layer are improved, and it is suitable for public places with large people.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350066A_ABST
    Figure CN119350066A_ABST
Patent Text Reader

Abstract

The invention relates to a digital slurry decorative ceramic tile with decorative durability and a preparation method thereof. The preparation method comprises the following steps: (1) drying a formed ceramic green body to obtain a dried green body; (2) spraying water on the surface of the dried blank to wet the blank surface; (3) arranging a water-based waterproof layer on the surface of the green body wetted by water spraying; (4) spraying water on the surface of the green body water-based waterproof layer to wet the green body surface; (5) decorating the green body of which the surface is wetted by water spraying according to a preset pattern by a slurry decoration technology to form a slurry decoration layer; (6) coating the bottom of the green body in the step (5) with prime slurry or arranging a dotted pattern layer and protective glaze on the surface of the green body in the step (5) and then coating the bottom of the green body with the prime slurry; (7) carrying out high-temperature firing on the blank coated with the prime pulp; and (8) directly edging the fired ceramic product or polishing and then edging the fired ceramic product to finally obtain a ceramic finished product brick.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic tile decoration, and particularly relates to a digital paste-decorated ceramic tile with decorative durability and a preparation method thereof. Background Art

[0002] Ceramic tiles have always been one of the important materials for home decoration and public place decoration because of their rich colors and patterns, beautiful decorative effects, and many excellent physical and chemical properties such as pollution resistance, wear resistance, high hardness, low radioactive pollution and easy cleaning.

[0003] The existing decorative processes for ceramic tiles are mainly flat-bed printing, rubber roller printing and inkjet printing. However, the thickness of the pattern decorative layer prepared by these three decorative processes is less than 0.05 mm. Compared with natural stone, the thickness of the decorative layer is too thin, and there is a gap in decorative durability. Long-term use can easily cause the loss of pattern texture, and it is difficult to meet the use requirements of public places with large traffic such as large shopping malls and subway stations. Therefore, natural stone decoration is still the main method in public places.

[0004] To improve this situation, the technical staff in the industry have improved the ceramic production process. From a technical point of view, there are two main methods: one is to cover the surface of the pattern decoration layer with a transparent protective glaze layer. Although the wear resistance of the surface can be improved by adding a transparent protective glaze layer, it will reduce the clarity of the decorative pattern and the presentation of details, affecting the overall decorative effect of the product; the other is to adopt the whole body fabric technology. Although this technology can increase the thickness of the decorative layer, the pattern texture is relatively rough, and it is impossible to achieve the same rich and three-dimensional pattern details as flat printing, rubber roller printing and inkjet printing. This is because the current whole body fabric technology basically uses 20-80 mesh coarse powder as the fabric medium, the decoration precision is low, and the layered three-dimensional sense of the texture pattern cannot be shown. Therefore, how to ensure the rich texture of the pattern while taking into account the durability of the decoration has become a problem that needs to be solved in the development of ceramic tiles. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a digital slurry-decorated ceramic tile with rich and fine patterns and textures, a decorative layer that is not easily worn or lost after long-term use, and decorative durability, and a preparation method thereof.

[0006] The technical solution of the present invention is the digital slurry-decorated ceramic tile with decorative durability, which is special in that the digital slurry-decorated slurry formula of the ceramic tile is composed of the following components by weight percentage: spodumene 0-6wt%, quartz powder 0-10wt%, corundum powder 0-10wt%, strontium carbonate 0-10wt%, barium carbonate 0-12wt%, potassium feldspar 0-25wt%, sodium feldspar 0-25wt%, water abrasive 0-30wt%, potassium sodium stone powder 0-40wt%, burned talc 3-8wt%, calcite 0-10 wt%, dolomite 0-10wt%, kaolin 5-15wt%, washed mud 0-15wt%, bentonite 0-6wt%, mixed mud 0-15wt%, calcined bauxite 0-8wt%, calcined kaolin 0-10wt%, zirconium silicate 0-10wt%, high potassium frit 0-25wt%, high calcium frit 0-15wt%, high barium frit 0-10wt%, high strontium frit 0-10wt%, carboxymethyl cellulose 0-1.0wt%, trimer 0.5-1.0wt%, defoamer 0.2-1wt%.

[0007] As a preference: the spodumene is Li 2 The O content is between 4 and 6 wt%, and the Al 2 O 3 20~25wt%, SiO 2 It is 68~78wt%.

[0008] As a preferred embodiment, the water-abrasive material is the raw material after the slag is flotated and desulfurized after the first lithium extraction, and the chemical composition is as follows by weight percentage: Al 2 O 3 15~20wt%、SiO 2 65~75wt%、K 2 O 2~5wt%, Fe 2 O 3 0~4wt%、Na 2 O 2~5wt%, CaO 0~2wt%, MgO 0~1wt%, Li 2 O 0.3~1wt%, trace elements ≥0.1wt%, SO 3 0~0.2wt%, ignition loss 0~5wt%; the trace elements include rubidium, gallium, strontium, cadmium and nickel.

[0009] As a preference: the K of the high potassium frit 2 O content is 13-18wt%, Na 2 O content is 3-6wt%, Al 2 O 3 The content is 17-23wt%, SiO 2The content of CaO is 4-8wt%, the content of MgO is 0.3-0.8wt%, and the content of Fe is 1. 2 O 3 The content is 0.03-0.1wt%;

[0010] The high calcium frit has a CaO content of 18-22wt%, Al 2 O 3 The content is 15-26wt%, SiO 2 The content is 50-60wt%, the MgO content is 2-4wt%, and the Fe 2 O 3 The content is 0.01~0.1wt%, K 2 O content is 2-4wt%, Na 2 O content is 0.5-1.5wt%, ZnO content is 1-3wt%;

[0011] The high-barium frit has a BaO content of 35-45wt%, Al 2 O 3 The content is 12-18wt%, SiO 2 The content is 35-45wt%, the CaO content is 2-4wt%, the MgO content is 0.2-0.5wt%, and the Fe 2 O 3 The content is 0.01~0.2wt%, K 2 O content is 0.2-0.5wt%, Na 2 O content is 2-5wt%;

[0012] The high strontium frit has a SrO content of 20-25wt%, Al 2 O 3 The content is 12-20wt%, SiO 2 The content is 50-55wt%, the CaO content is 3-8wt%, the MgO content is 2-6wt%, and the Fe 2 O 3 The content is 0.01~0.1wt%, K 2 O content is 1.5-3.0wt%, Na 2 The O content is 1.5 to 3.0 wt%.

[0013] Another technical solution of the present invention is a method for preparing the digital paste-decorated ceramic tile with decorative durability, which is special in that it includes the following steps:

[0014] (1) drying the formed ceramic body to obtain a dried body;

[0015] (2) Spray water on the surface of the dried green body to moisten the green body;

[0016] (3) Arrange a water-based water-blocking layer on the surface of the green body wetted by water spraying;

[0017] (4) Spray water on the surface of the water-based water-blocking layer of the blank to wet the blank surface;

[0018] (5) The blank with the surface wetted by water is decorated by digital slurry decoration process according to a preset pattern to form a slurry decoration layer;

[0019] (6) Applying a base slurry to the bottom of the green body in step (5) or applying a base slurry to the bottom of the green body after applying a dot pattern layer and a protective glaze to the surface of the green body in step (5);

[0020] ⑺The green body after coating with base slurry is fired at high temperature;

[0021] ⑻ Grind the edges of the fired ceramic products directly or polish them and then grind them to finally obtain finished ceramic tiles.

[0022] As a preferred embodiment, the water-blocking layer formulation in step (3) is composed of the following components by weight percentage: 10-20wt% water-based water-blocking agent, 1-3wt% emulsifier, 1-3wt% stabilizer, 1-3wt% defoamer, 60-80wt% free water, and 1-3wt% dispersant;

[0023] The water-based water-blocking layer is arranged by a spray gun process, the nozzle aperture of the spray gun is set to 0.5-0.8 mm, and the specific gravity of the water-blocking solution is set to 1.1-1.3 g / cm 3 , the spraying amount is set to 10~20g / m 2 ;

[0024] The water-based water-blocking agent is composed of one or more of hydrogenated polysilicone oil, dimethyl silicone oil, methyl trisiloxane, ethyl trisiloxane, silane propyl ether, fluorocarbon resin, polyvinyl fluoride, epoxy resin, polyurethane, polyester, alkyd resin, acrylic acid, polyacrylic acid, polyvinyl alcohol, and polyamide;

[0025] The emulsifier is composed of one or more of oleyl alcohol polyether, stearate, cetearyl glucose, methyl glucose sesquistearate, sodium stearoyl glutamate, carboxylates, sulfates, sulfonates, N-dodecyl dimethylamine, polyoxyethylene ethers, sucrose esters, polyglycerol esters, calcium stearoyl lactylate, fatty acid soaps, sodium lauryl sulfate, sodium dodecylbenzene sulfonate, phosphates, and hexaglycerol monocaprylate;

[0026] The stabilizer is composed of one or more of gelatin, sodium carboxymethyl cellulose, xanthan gum, dextrin, sodium gelatinate, polysorbate 20, sodium silicate, sodium benzoate, and carrageenan.

[0027] As a preferred embodiment, the digital paste decoration process described in step (5) comprises the following steps:

[0028] (5.1) Prepare the formula materials according to the slurry formula of digital slurry decoration;

[0029] (5.2) adding water to the formula material and subjecting it to graded ball milling, wherein the graded ball milling includes primary wet ball milling and secondary wet ball milling; stirring the slurry after the primary wet ball milling uniformly and then sending it to a spray drying tower for powdering to obtain a primary formula powder and storing it for aging for later use;

[0030] (5.3) The obtained primary formula powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1050-1150°C to obtain a light-burned material. In order to ensure the subsequent secondary ball milling process, the strength of the calcined light-burned material is controlled to be <5Mpa;

[0031] (5.4) Adding pigments of different colors in different proportions to the light-burned material according to the design, adding water to the light-burned material after adding the pigments to perform secondary wet ball milling to obtain slurries of different colors;

[0032] (5.5) The milled slurries of different colors are loaded into a slurry decoration device; the slurry decoration device uses digital information to directly control the printing equipment, which can realize the printing of 4 to 10 different color slurries at the same time, and the printing amount per square meter is 850g to 1800g;

[0033] (5.6) Input a preset pattern texture into the slurry decoration device, and use different color slurries to carry out slurry decoration design on the surface of the ceramic body to form a decorative layer with wear-resistant, anti-slip, light-transmitting, soft light, and delicate effects; the thickness of the decorative layer formed by the slurry decoration technology is between 0.5mm and 1.0mm.

[0034] As a preference: the slurry formula of the digital slurry decoration described in step (5.1) is composed of the following components by weight percentage: spodumene 0-6wt%, quartz powder 0-10wt%, corundum powder 0-10wt%, strontium carbonate 0-10wt%, barium carbonate 0-12wt%, potassium feldspar 0-25wt%, sodium feldspar 0-25wt%, water abrasive 0-30wt%, potassium sodium stone powder 0-40wt%, burned talc 3-8wt%, calcite 0-10wt%, dolomite 0-10wt% , kaolin 5~15wt%, washed mud 0~15wt%, bentonite 0~6wt%, mixed mud 0~15wt%, calcined bauxite 0~8wt%, calcined kaolin 0~10wt%, zirconium silicate 0~10wt%, high potassium frit 0~25wt%, high calcium frit 0~15wt%, high barium frit 0~10wt%, high strontium frit 0~10wt%, carboxymethyl cellulose 0~1.0wt%, trimer 0.5~1.0wt%, defoamer 0.2~1wt%.

[0035] As a preference: the spodumene is Li 2The O content is between 4 and 6 wt%, and the Al 2 O 3 20~25wt%, SiO 2 68-78wt%;

[0036] The water-abrasive material is the raw material after the slag is flotated and desulfurized after the first lithium extraction, and the chemical composition is as follows by weight percentage: Al 2 O 3 15~20wt%、SiO 2 65~75wt%、K 2 O 2~5wt%, Fe 2 O 3 0~4wt%、Na 2 O 2~5wt%, CaO 0~2wt%, MgO 0~1wt%, Li 2 O 0.3~1wt%, trace elements ≥0.1wt%, SO 3 0-0.2wt%, ignition loss 0-5wt%; the trace elements include rubidium, gallium, strontium, cadmium, and nickel;

[0037] The K of the high potassium frit 2 O content is 13-18wt%, Na 2 O content is 3-6wt%, Al 2 O 3 The content is 17-23wt%, SiO 2 The content of CaO is 4-8wt%, the content of MgO is 0.3-0.8wt%, and the content of Fe is 1. 2 O 3 The content is 0.03-0.1wt%;

[0038] The high calcium frit has a CaO content of 18-22wt%, Al 2 O 3 The content is 15-26wt%, SiO 2 The content is 50-60wt%, the MgO content is 2-4wt%, and the Fe 2 O 3 The content is 0.01~0.1wt%, K 2 O content is 2-4wt%, Na 2 O content is 0.5-1.5wt%, ZnO content is 1-3wt%;

[0039] The high-barium frit has a BaO content of 35-45wt%, Al 2 O 3 The content is 12-18wt%, SiO 2The content is 35-45wt%, the CaO content is 2-4wt%, the MgO content is 0.2-0.5wt%, and the Fe 2 O 3 The content is 0.01~0.2wt%, K 2 O content is 0.2-0.5wt%, Na 2 O content is 2-5wt%;

[0040] The high strontium frit has a SrO content of 20-25wt%, Al 2 O 3 The content is 12-20wt%, SiO 2 The content is 50-55wt%, the CaO content is 3-8wt%, the MgO content is 2-6wt%, and the Fe 2 O 3 The content is 0.01~0.1wt%, K 2 O content is 1.5-3.0wt%, Na 2 The O content is 1.5 to 3.0 wt%.

[0041] Preferably, in the first-stage wet ball milling of step (5.2), the moisture content of the raw material entering the ball is ≤3wt%, the residue on the 200-mesh sieve is ≤8wt%, the ratio of material: ball: water is 1:2.5:0.36, the ball stones and ball lining used in the ball mill are all made of high-aluminum materials, and the ball stone grading is: Φ60mm accounts for 5wt%, Φ50mm accounts for 20wt%, Φ40mm accounts for 45wt%, Φ30mm accounts for 30wt%, and the fineness of the slurry after the first-stage ball milling is 325-mesh sieve residue between 1.5 and 3.0wt%;

[0042] The spray drying tower in step (5.2) adopts a pressure spray drying system, the spray tower uses a nozzle sheet combination with an aperture of 1.5mm to 2.0mm, the atomization pressure is 1.8MPa to 2.6MPa, the diameter of the drying chamber is greater than 10m, the drying output is 10-30t / h, and the particle gradation of the obtained powder is: the particles on the 20-mesh sieve account for 0-6wt%, the particles between 20-mesh and 40-mesh account for 30-40wt%, the particles between 40-mesh and 60-mesh account for 40-45wt%, the particles between 60-mesh and 80-mesh account for 15-25wt%, the particles below 80-mesh account for 0-3%, and the specific gravity of the powder is 0.85-0.95g / cm 3 , the moisture content is controlled to be: 6-8wt%, and the angle of repose is controlled to be 33°-38°;

[0043] In step (5.3), colorants of different colors are added to the light-burned material, and then secondary wet ball milling is performed; the secondary wet ball milling requires that material: ball: water = 1:2.5:0.38, the ball stone and ball lining used in the ball mill are all made of high-aluminum material, and the ball stone grading is: Φ8mm accounts for 10wt%, Φ4mm accounts for 30wt%, Φ3mm accounts for 40wt%, Φ2mm accounts for 20wt%, and the slurry after secondary ball milling has a specific gravity of 1.75±0.5g / cm 3 , 40° viscosity is 60~150mpa.s, D50 particle size is 5μm~15μm;

[0044] The slurries of different colors include ceramic pigments of different colors such as white, blue, brown, red, yellow, black and green; the white one is zirconium silicate.

[0045] As a preferred embodiment: the formula of the dot pattern layer of step (6) is composed of the following components by weight percentage: 15-25wt% of colored dry particles, 3-6wt% of flash point, 50-60wt% of suspension, 1-3wt% of defoamer, 10-20wt% of free water, and 1-3wt% of dispersant;

[0046] The dot pattern layer is arranged by a dot-spraying device, the dot-spraying device has a dot-spraying head set to a mesh or disc type, an operating frequency set to 50-200 Hz, and a dot-spraying solution with a specific gravity set to 1.2-1.4 g / cm 3 , the application rate is set to 15-25g / m 2 ;

[0047] The colored dry particles are composed of one or more of white dry particles, yellow dry particles, brown dry particles, red dry particles, black dry particles, green dry particles, blue dry particles, transparent dry particles, apricot dry particles, and gray dry particles;

[0048] The particle grading of the colored dry particles is controlled such that particles on a 20-mesh sieve account for 0-3wt%, particles between 20-40 mesh account for 40-50wt%, particles between 40-60 mesh account for 25-35wt%, particles between 60-80 mesh account for 20-25wt%, and particles below 80 mesh account for 0-1wt%;

[0049] The flash point is composed of muscovite, phlogopite, biotite, lepidolite, sericite, green mica and iron lithium mica, hard rock mica, iron sulfide, baddeleyite , zirconite, Green Zircon , andalusite, kyanite or more;

[0050] The particle grading of the flash point is controlled as follows: particles on the 12 mesh sieve account for 0-5wt%, particles between 12 mesh and 20 mesh account for 35-45wt%, particles between 20 mesh and 40 mesh account for 10-20wt%, particles between 40 mesh and 60 mesh account for 20-25wt%, particles between 60 mesh and 80 mesh account for 15-20wt%, and particles below 80 mesh account for 0-1wt%.

[0051] Another technical solution of the present invention is that the digital paste-decorated ceramic tile with decorative durability is prepared by any of the aforementioned preparation methods.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] ⑴ The present invention calcines and fires the formula and sets a suitable firing temperature. While ensuring the processing performance of the material after firing, the wear resistance, light transmittance, comfort and other properties of the slurry are improved, and ceramic colorants are introduced into the formula material. Ceramic slurries of different colors are obtained after ball milling. The CNC slurry decoration process is used to achieve decorative patterns with a thickness of up to 0.8 mm or more. The ultra-thick decorative layer makes the surface hardness and wear resistance of the product significantly exceed those of ceramic tiles prepared by processes such as flat plate printing, rubber roller printing and inkjet printing. The product not only has rich and fine pattern textures, but also has ultra-long decorative durability, which greatly broadens the scope of application.

[0054] (2) The present invention adopts a two-stage ball milling process to prepare the slurry for slurry decoration technology. Different ball milling parameters are used in the first and second stages. While improving the ball milling efficiency of the raw materials, the various properties of the slurry are effectively improved to meet the performance requirements of the CNC spraying process for the mud.

[0055] ⑶ The present invention cooperates with the digital paste decoration process to achieve high-precision pattern texture and better decorative durability, and also can achieve functional effects such as wear resistance, anti-slip, light transmission, and soft and delicate light, including:

[0056] (3.1) When the paste formula of digital paste is SiO 2 The content is between 45 and 55 wt%, Al 2 O 3 When the content is 25-35wt%, by introducing corundum powder, water abrasive, zirconium silicate and coordinating with other raw materials, the formation of high hardness crystal phases such as mullite, corundum, zircon, quartz and feldspar can be promoted to improve wear resistance; the corundum powder of this formula is finely ground to a D50 between 1μm and 3μm, and a wear-resistant and non-slip product with a PTV value of more than 60 and a comfortable texture can be achieved.

[0057] (3.2) When the slurry formula of digital slurry is SiO 2 The content is between 50 and 55 wt%, Al 2O 3 When the content is 14-18wt%, by introducing strontium carbonate, barium carbonate, burned talc, dolomite, high calcium frit, high barium frit, high strontium frit, and other raw materials, the formation of crystal phases such as calcium and celsium feldspar can be promoted, so that the surface forms a soft and delicate surface texture of 10° to 20°.

[0058] (3.3) When the paste formula of digital paste is SiO 2 The content is between 60 and 68 wt%, Al 2 O 3 When the content is 15-20wt%, by introducing quartz powder, high potassium frit and high barium frit, in combination with other raw materials, it can promote the formation of crystals such as barium feldspar, barium cryolite, and quartz whose refractive index is very close to that of ceramic glass, and combine with slurry decoration technology to form products with light-set decorative patterns.

[0059] ⑷ The functions of the graded ball milling of the present invention are: ① improving the ball milling efficiency and saving the power consumption of the ball milling; ② avoiding over-grinding of the soft raw materials in the formula, thereby affecting the particle size distribution and flow properties of the slurry; ③ avoiding the ball milling time being too long, thereby destroying the inclusions of the encapsulated colorant and affecting the color of the encapsulated colorant. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is a remaining image of the decorative layer pattern after polishing in Example 1 of the present invention;

[0061] Figure 2 This is a residual pattern of the decorative layer after polishing in Example 1;

[0062] Figure 3 This is a residual pattern of the decorative layer after polishing in Example 2;

[0063] Figure 4 This is a residual pattern of the decorative layer after polishing in Example 2;

[0064] Figure 5 This is a diagram showing the physical phase detection results of the ceramic tile of Example 1 of the present invention;

[0065] Figure 6 This is a diagram showing the physical phase detection results of the ceramic tile of Example 2 of the present invention;

[0066] Figure 7 This is a diagram of the physical phase detection results of the ceramic tile of Example 3 of the present invention. DETAILED DESCRIPTION

[0067] The present invention will be further described in detail below in conjunction with embodiments:

[0068] Example 1

[0069] The digital spraying process with decorative durability includes the following steps:

[0070] (1) drying the formed ceramic body to obtain a dried body;

[0071] (2) Spray water on the surface of the dried green body to moisten the green body;

[0072] (3) Arrange a water-based water-blocking layer on the surface of the green body wetted by water spraying;

[0073] The water-based water-blocking layer formula is composed of the following components by weight percentage: 17wt% water-based water-blocking agent, 2wt% emulsifier, 2wt% stabilizer, 1wt% defoamer, 76wt% free water, and 2wt% dispersant;

[0074] The free water refers to the water that exists on the surface, pores or coarse capillaries of the material and is not bound by the colloid of the material. It is mechanically mixed with the material and is also called mechanically bound water. "Ceramic Technology": "Free water is also called mechanically bound water. It is between the particles of the green body, making the particles separate from each other but not connected." The binding force between free water and the material is weak and it is easy to remove during the drying process. As the free water is continuously removed, the material particles will gradually move closer, causing the green body to shrink.

[0075] The water-based water-blocking layer is arranged by spray gun technology, the nozzle aperture of the spray gun is set to 0.72 mm, and the specific gravity of the water-blocking solution is set to 1.2 g / cm 3 , the spraying rate is set to 15g / m 2 ;

[0076] The water-based water-blocking agent is composed of the following raw material components: 50 parts of methyl trisiloxane and 50 parts of dimethyl silicone oil;

[0077] The emulsifier is composed of the following raw material components: 70 parts of sodium lauryl sulfate and 30 parts of phosphate;

[0078] The stabilizer is composed of the following raw material components: 100 parts of sodium carboxymethyl cellulose.

[0079] (4) Spray water on the surface of the water-based water-blocking layer of the blank to wet the blank surface;

[0080] (5) The blank with the surface wetted by water is decorated by digital slurry decoration process according to a preset pattern to form a slurry decoration layer;

[0081] The digital paste decoration process comprises the following steps:

[0082] (5.1) Prepare the material according to the slurry formula of digital slurry decoration.

[0083] The slurry formula of the digital slurry decoration consists of the following components by weight percentage: 10wt% of corundum powder, 13.5wt% of water abrasive, 21wt% of potassium sodium stone powder, 3wt% of burned talc, 11wt% of kaolin, 13.5wt% of washed mud, 4.5wt% of bentonite, 11wt% of mixed mud, 5.5wt% of calcined aluminum vanadium, 6wt% of zirconium silicate, 0.6wt% of trimer, and 0.4wt% of defoamer.

[0084] The water-abrasive material is the raw material after the slag is flotated and desulfurized after the primary lithium extraction, and the chemical composition is as follows by weight percentage: Al 2 O 3 17.80wt%, SiO 2 69.05wt%, K 2 O 3.50wt%, Fe 2 O 3 0.87wt%, Na 2 O 3.45wt%, CaO0.84wt%, MgO 0.42wt%, Li 2 O 0.41wt%, trace elements 0.18wt%, SO 3 0.08wt%, loss on ignition 3.40wt%; trace elements include special elements such as rubidium, gallium, strontium, cadmium, nickel, etc.

[0085] The slurry formula of the digital slurry decoration contains SiO 2 Content 54.85wt%, Al 2 O 3 The content is 30.55wt%, CaO content is 0.32wt%, MgO content is 1.23wt%, Fe 2 O 3 The content is 0.33wt%, K 2 O content is 2.15wt%, Na 2 O content is 1.15wt%, ZrO 2 The content is 3.92wt%, and the ignition loss is 5.50wt%. The particle size of the corundum powder is finely ground to D50 of 2μm.

[0086] (5.2) Add water to the formula material and perform graded ball milling, wherein the graded ball milling includes primary wet ball milling and secondary wet ball milling; the slurry after the primary wet ball milling is stirred evenly and then sent to a spray drying tower for powdering to obtain a primary formula powder and store it for aging before use.

[0087] The spray drying tower adopts a pressure spray drying system. The spray tower uses a nozzle sheet combination with an aperture of 1.5 mm, an atomization pressure of 2.2 MPa, a drying chamber diameter greater than 10 m, a drying output of 15 t / h, and the particle gradation of the obtained powder is: the particles on the 20-mesh sieve account for 4 wt%, the particles between 20 and 40 meshes account for 36 wt%, the particles between 40 and 60 meshes account for 40 wt%, the particles between 60 and 80 meshes account for 18 wt%, and the particles below 80 meshes account for 2 wt%. The specific gravity of the powder is 0.91 g / cm 3 , the moisture content is controlled to be: 7.2wt%, and the angle of repose is controlled to be 35°.

[0088] (5.3) The obtained primary formula powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1080°C to obtain a light-burned material. In order to ensure the subsequent secondary ball milling process, the strength of the calcined light-burned material is 4.0Mpa;

[0089] (5.4) 10 wt% of white colorant (zirconium silicate), 1.5 wt% of cobalt blue colorant, 3.0 wt% of brown colorant, 5.0 wt% of encapsulated red colorant, 4.0 wt% of orange colorant, 5.0 wt% of encapsulated yellow colorant, and 1.5 wt% of black colorant are added to the light-burned material, and slurries of different colors are obtained by secondary wet ball milling;

[0090] The material of the secondary wet ball milling is ball: water = 1:2.5:0.38. The ball stones and ball linings used in the ball mill are all made of high-aluminum materials. The ball stone grading is: Φ8mm accounts for 10wt%, Φ4mm accounts for 30wt%, Φ3mm accounts for 40wt%, Φ2mm accounts for 20wt%, and the specific gravity of the slurry after the secondary ball milling is 1.75g / cm 3 , 40° viscosity is 112mpa.s, D50 particle size is 10.42μm;

[0091] (5.5) Loading the milled slurries of different colors into the slurry decoration device;

[0092] The paste decoration device is a device that uses digital information to directly control the printing, which can realize the printing of 7 different colors of paste at the same time, with a printing volume of 1600g per square meter;

[0093] (5.6) Inputting a preset pattern texture into the slurry decoration device, using different color slurries to carry out slurry decoration design on the surface of the ceramic body to form a wear-resistant and anti-slip pattern decoration layer;

[0094] The thickness of the decorative layer formed by the slurry decoration technology is between 0.85 mm;

[0095] (6) Applying slurry to the bottom of the blank in step (5);

[0096] ⑺The green body after coating with base slurry is fired at high temperature;

[0097] ⑻ Grind the edges of the fired ceramic products directly to finally obtain finished ceramic tiles.

[0098] The slurry formula of the digital spraying in this embodiment has a comfortable texture, wear resistance and anti-slip effect, and the PTV value is 63.

[0099] Comparative Example 1

[0100] A method for preparing a digital paste-decorated ceramic tile with decorative durability comprises the following steps:

[0101] (1) drying the formed ceramic body to obtain a dried body;

[0102] (2) Spray water on the surface of the dried green body to moisten the green body;

[0103] (3) The base glaze is decorated by spraying glaze or pouring glaze on the body with the surface wetted by water;

[0104] (4) Using flat screen printing to decorate the surface of the base glaze decorated body to form a decorative layer;

[0105] The flat screen printing, the flower screen is 80 mesh thickened three times, the number of printing times is 3 times, the specific gravity of the printed flower glaze is 1.40g / cm 3 The weight of the printed glaze after firing is 86.52g / m 2 , the thickness of the decorative layer formed by flat screen printing technology is between 0.11mm;

[0106] (5) Carry out glaze decoration on the blank of the flat decorative layer;

[0107] (6) Apply base slurry to the bottom of the body after glaze decoration;

[0108] ⑺The green body after coating with base slurry is fired at high temperature;

[0109] ⑻ Polish and grind the edges of the fired ceramic products to finally obtain finished ceramic tiles.

[0110] The difference between Comparative Example 1 and Example 1 is that the digital spraying method for forming the decorative layer in Example 1 is replaced by base glaze + flat screen printing, and a layer of top glaze is applied on the decorative layer for protection. The other preparation methods of Comparative Example 1 are the same as those of Example 1.

[0111] Comparative Example 2

[0112] A method for preparing a digital paste-decorated ceramic tile with decorative durability comprises the following steps:

[0113] (1) drying the formed ceramic body to obtain a dried body;

[0114] (2) Spray water on the surface of the dried green body to moisten the green body;

[0115] (3) The base glaze is decorated by spraying glaze or pouring glaze on the body with the surface wetted by water;

[0116] (4) Using roller printing to decorate the surface of the base glaze decorated body to form a decorative layer;

[0117] The roller printing has a roller engraving aperture of 0.5 mm, an engraving angle of 45°, a printing number of 5 times, and a specific gravity of the printed glaze of 1.50 g / cm 3 The weight of the printed glaze after firing is 6.86g / m 2 , the thickness of the decorative layer formed by roller printing technology is between 0.04mm;

[0118] (5) Carry out glaze decoration on the blank of the roller decoration layer;

[0119] (6) Apply base slurry to the bottom of the body after glaze decoration;

[0120] ⑺The green body after coating with base slurry is fired at high temperature;

[0121] ⑻ Polish and grind the edges of the fired ceramic products to finally obtain finished ceramic tiles.

[0122] The difference between Comparative Example 2 and Example 1 is that the digital spraying method for forming the decorative layer in Example 1 is replaced by base glaze + roller printing, and a layer of top glaze is applied on the decorative layer for protection. The other preparation methods of Comparative Example 2 are the same as those of Example 1.

[0123] Comparative Example 3

[0124] A method for preparing a digital paste-decorated ceramic tile with decorative durability comprises the following steps:

[0125] (1) drying the formed ceramic body to obtain a dried body;

[0126] (2) Spray water on the surface of the dried green body to moisten the green body;

[0127] (3) The base glaze is decorated by spraying glaze or pouring glaze on the body with the surface wetted by water;

[0128] (4) Decorate the surface of the base glaze decorated body by inkjet printing to form a decorative layer;

[0129] The inkjet printing adopts Seiko 1536M nozzle, the average grayscale of the printed document of the channel is 60%, and the ink specific gravity is 1.12g / cm 3 The printing pattern is designed with 8 channels, and the ink weight after burning is 12.65g / m 2, the thickness of the decorative layer formed by inkjet printing technology is between 0.02mm;

[0130] (5) Carrying out glaze decoration on the body of the inkjet decorative layer;

[0131] (6) Apply base slurry to the bottom of the body after glaze decoration;

[0132] ⑺The green body after coating with base slurry is fired at high temperature;

[0133] ⑻ Polish and grind the edges of the fired ceramic products to finally obtain finished ceramic tiles.

[0134] The difference between Comparative Example 3 and Example 1 is that the decorative layer formed by the slurry decoration technology in Example 1 is replaced by the decorative layer formed by the base glaze + inkjet printing, and a layer of top glaze is applied on the decorative layer for protection. The other preparation methods of Comparative Example 3 are the same as those of Example 1.

[0135] Specifically, samples were prepared by the methods of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively, and were placed in a roller kiln at a temperature of 1200° C. for calcination for 60 min. The surface of the fired sample was polished using a polishing machine. The polishing machine parameters were a pressure of 0.4 MPa, a polishing speed of 20 m / min, and a polishing abrasive block combination of 12 groups of 400-mesh elastic abrasive blocks, 18 groups of 600-mesh elastic abrasive blocks, 20 groups of 800-mesh elastic abrasive blocks, 6 groups of 1000-mesh fiber abrasive blocks, and 8 groups of 1500-mesh fiber abrasive blocks. The polishing cutting amount was between 0.03 and 0.04 mm. The results are shown in Table 1 below:

[0136] Table 1 Comparison of polishing of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3

[0137]

[0138] The polishing comparison test results of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are combined Figure 1 to Figure 4 It can be seen that the decorative pattern of the product prepared by Example 1 is complete without any defects, while the decorative patterns of the samples prepared by the processes of Comparative Examples 1, 2 and 3 have been completely worn out with almost nothing remaining, indicating that the ceramic product prepared by the digital spraying process of the present invention has significantly improved wear resistance of the decorative layer and has better decorative durability.

[0139] Example 2

[0140] A method for preparing a digital paste-decorated ceramic tile with decorative durability comprises the following steps:

[0141] (1) drying the formed ceramic body to obtain a dried body;

[0142] (2) Spray water on the surface of the dried green body to moisten the green body;

[0143] (3) Arrange a water-based water-blocking layer on the surface of the green body wetted by water spraying;

[0144] The aqueous water-blocking layer formula is composed of the following components by weight percentage: 17wt% aqueous water-blocking agent, 2wt% emulsifier, 2wt% stabilizer, 1wt% defoamer, 76wt% free water, and 2wt% dispersant.

[0145] The water-based water-blocking layer is arranged by spray gun technology, the nozzle aperture of the spray gun is set to 0.72 mm, and the specific gravity of the water-blocking solution is set to 1.2 g / cm 3 , the spraying rate is set to 15g / m 2

[0146] The water-based water-blocking agent is composed of the following raw material components by weight: 50 parts of methyl trisiloxane and 50 parts of dimethyl silicone oil;

[0147] The emulsifier is composed of the following raw material components by weight: 70 parts of sodium lauryl sulfate and 30 parts of phosphate;

[0148] The stabilizer is composed of the following raw material components: 100 parts of sodium carboxymethyl cellulose;

[0149] (4) Spray water on the surface of the water-based water-blocking layer of the blank to wet the blank surface;

[0150] (5) The blank with the surface wetted by water is decorated by digital slurry decoration process according to a preset pattern to form a slurry decoration layer;

[0151] The digital paste decoration process comprises the following steps:

[0152] (5.1) Prepare the material according to the slurry formula of digital slurry decoration.

[0153] The slurry formula of the digital slurry decoration consists of the following components by weight percentage: quartz powder 10wt%, potassium feldspar 18.5wt%, water abrasive 5wt%, calcined talc 4wt%, calcite 1wt%, kaolin 15wt%, washed mud 6wt%, bentonite 6wt%, high potassium frit 23wt%, high barium frit 10wt%, carboxymethyl cellulose 0.42wt%, trimer 0.6wt%, and defoamer 0.48wt%.

[0154] The water-abrasive material is a raw material obtained by flotation and desulfurization of slag after primary lithium extraction, and its chemical composition is composed of the following components by weight percentage: Al 2 O 3 17.80wt%, SiO 2 69.05wt%, K 2 O 3.50wt%, Fe 2O 3 0.87wt%, Na 2 O 3.45wt%, CaO 0.84wt%, MgO 0.42wt%, Li 2 O 0.41wt%, trace elements 0.18wt%, SO 3 0.08wt%, loss on ignition 3.40wt%; trace elements include special elements such as rubidium, gallium, strontium, cadmium, nickel, etc.

[0155] The high potassium frit SiO 2 Content 54.87wt%, Al 2 O 3 The content is 18.24wt%, CaO content is 6.08wt%, MgO content is 0.46wt%, Fe 2 O 3 The content is 0.06wt%, K 2 O content is 14.72wt%, Na 2 The O content is 5.57wt%.

[0156] The high-barium frit is SiO 2 Content 38.63wt%, Al 2 O 3 The content is 15.08wt%, CaO content is 2.98wt%, MgO content is 0.26wt%, Fe 2 O 3 The content is 0.03wt%, K 2 O content is 0.35wt%, Na 2 The O content is 3.69wt%, and the BaO content is 38.98wt%.

[0157] The slurry formula of the digital slurry decoration contains SiO 2 Content 61.41wt%, Al 2 O 3 The content is 18.02wt%, CaO content is 2.59wt%, MgO content is 1.63wt%, Fe 2 O 3 The content is 0.22wt%, K 2 O content is 5.88wt%, Na 2 The O content is 2.42wt%, the BaO content is 3.96wt%, and the loss on ignition is 3.87wt%.

[0158] (5.2) adding water to the formula material and subjecting it to graded ball milling, wherein the graded ball milling includes primary wet ball milling and secondary wet ball milling; stirring the slurry after the primary wet ball milling uniformly and then sending it to a spray drying tower for powdering to obtain a primary formula powder and storing it for aging for later use;

[0159] In the first-stage wet ball milling, the moisture content of the raw material entering the ball is 2.3wt%, the residue on the 200-mesh sieve is 7wt%, the material: ball: water = 1:2.5:0.36, the ball stones and ball linings used in the ball mill are all made of high-aluminum material, the ball stone grading is: Φ60mm accounts for 5wt%, Φ50mm accounts for 20wt%, Φ40mm accounts for 45wt%, Φ30mm accounts for 30wt%, and the fineness of the slurry after the first-stage ball milling is between 325-mesh sieve residue and 2.46wt%.

[0160] The spray drying tower adopts a pressure spray drying system. The spray tower uses a nozzle sheet combination with an aperture of 1.5 mm, an atomization pressure of 2.2 MPa, a drying chamber diameter greater than 10 m, a drying output of 15 t / h, and the particle gradation of the obtained powder is: the particles on the 20-mesh sieve account for 4 wt%, the particles between 20 and 40 meshes account for 36 wt%, the particles between 40 and 60 meshes account for 40 wt%, the particles between 60 and 80 meshes account for 18 wt%, and the particles below 80 meshes account for 2 wt%. The specific gravity of the powder is 0.91 g / cm 3 , the moisture content is controlled to be: 7.2wt%, and the angle of repose is controlled to be 35°.

[0161] (5.3) The obtained primary formula powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1080°C to obtain a light-burned material. In order to ensure the subsequent secondary ball milling process, the strength of the calcined light-burned material is 4.0Mpa;

[0162] (5.4) 0.5wt% of white colorant (zirconium silicate), 1.5wt% of cobalt blue colorant, 3.0wt% of brown colorant, 5.0wt% of wrapped red colorant, 4.0wt% of orange colorant, 5.0wt% of wrapped yellow colorant, 1.5wt% of black colorant, and 0.5wt% of green colorant are added to the light-burned material, and slurries of different colors are obtained by secondary wet ball milling;

[0163] The material of the secondary wet ball milling is ball: water = 1:2.5:0.38. The ball stones and ball linings used in the ball mill are all made of high-aluminum materials. The ball stone grading is: Φ8mm accounts for 10wt%, Φ4mm accounts for 30wt%, Φ3mm accounts for 40wt%, Φ2mm accounts for 20wt%, and the specific gravity of the slurry after the secondary ball milling is 1.75g / cm 3 , 40° viscosity is 86mpa.s, and D50 particle size is 8.76μm.

[0164] (5.5) Loading the milled slurries of different colors into the slurry decoration device;

[0165] The paste decoration equipment is a device that uses digital information to directly control printing. This technology can realize the printing of 8 different colors of paste at the same time, with a printing volume of 1600g per square meter;

[0166] (5.6) Inputting a preset pattern texture into the slurry decoration equipment, using white slurry and slurries of different colors to carry out slurry decoration design on the surface of the ceramic body, and forming a decorative layer with a light-set decorative pattern;

[0167] The thickness of the decorative layer formed by digital spraying is between 0.85 mm;

[0168] (6) Apply base slurry to the bottom of the body after surface decoration;

[0169] ⑺ Firing the green body after coating the base slurry at high temperature;

[0170] ⑻ Grind the edges of the fired products directly.

[0171] Example 3

[0172] A method for preparing a digital paste-decorated ceramic tile with decorative durability comprises the following steps:

[0173] (1) drying the formed ceramic body to obtain a dried body;

[0174] (2) Spray water on the surface of the dried green body to moisten the green body;

[0175] (3) Arrange a water-based water-blocking layer on the surface of the green body wetted by water spraying;

[0176] The aqueous water-blocking layer formula is composed of the following components by weight percentage: 17wt% aqueous water-blocking agent, 2wt% emulsifier, 2wt% stabilizer, 1wt% defoamer, 76wt% free water, and 2wt% dispersant.

[0177] The water-based water-blocking layer is arranged by spray gun technology, the nozzle aperture of the spray gun is set to 0.72 mm, and the specific gravity of the water-blocking solution is set to 1.2 g / cm 3 , the spraying rate is set to 15g / m 2

[0178] The water-based water-blocking agent is composed of the following raw material components by weight: 50 parts of methyl trisiloxane and 50 parts of dimethyl silicone oil;

[0179] The emulsifier is composed of the following raw material components by weight: 70 parts of sodium lauryl sulfate and 30 parts of phosphate;

[0180] The stabilizer is composed of the following raw material components by weight: 100 parts of sodium carboxymethyl cellulose;

[0181] (4) Spray water on the surface of the water-based water-blocking layer of the blank to wet the blank surface;

[0182] (5) The blank with the surface wetted by water is decorated by digital slurry decoration process according to a preset pattern to form a slurry decoration layer;

[0183] The digital paste decoration process comprises the following steps:

[0184] (5.1) Prepare the material according to the slurry formula of digital slurry decoration.

[0185] The slurry formula of the digital slurry decoration consists of the following components in weight percentage: calcined zinc oxide 4wt%, barium carbonate 3wt%, potassium feldspar 21wt%, sodium feldspar 15wt%, burned talc 8wt%, dolomite 7wt%, kaolin 8wt%, calcined kaolin 6.5wt%, high calcium frit 15wt%, high barium frit 8wt%, high strontium frit 3wt%, carboxymethyl cellulose 0.39wt%, trimer 0.63wt%, and defoamer 0.48wt%.

[0186] The high calcium frit SiO 2 The content is 54.14wt%, Al 2 O 3 The content is 18.30wt%, CaO content is 19.64wt%, MgO content is 2.62wt%, Fe 2 O 3 The content is 0.03wt%, K 2 O content is 2.68wt%, Na 2 The O content is 0.91wt%, and the ZnO content is 1.68wt%.

[0187] The high barium frit SiO 2 The content is 38.63wt%, Al 2 O 3 The content is 15.08wt%, CaO content is 2.98wt%, MgO content is 0.26wt%, Fe 2 O 3 The content is 0.03wt%, K 2 O content is 0.35wt%, Na 2 The O content is 3.69wt%, and the BaO content is 38.98wt%.

[0188] The high strontium frit SiO 2 The content is 51.32wt%, Al 2 O 3 The content is 14.61wt%, CaO content is 5.30wt%, MgO content is 3.20wt%, Fe 2 O 3 The content is 0.05wt%, K 2O content is 1.96wt%, Na 2 The O content is 2.34wt%, and the SrO content is 21.22wt%.

[0189] The slurry formula of the digital slurry decoration contains SiO 2 The content is 51.31wt%, Al 2 O 3 The content is 16.74wt%, the CaO content is 6.01wt%, the MgO content is 4.71wt%, and the Fe 2 O 3 The content is 0.13wt%, K 2 O content is 2.83wt%, Na 2 The O content is 2.53wt%, the BaO content is 5.53wt%, the SrO content is 0.65wt%, the ZnO content is 4.33wt%, and the loss on ignition is 5.23wt%.

[0190] (5.2) adding water to the formula material and subjecting it to graded ball milling, wherein the graded ball milling includes primary wet ball milling and secondary wet ball milling; stirring the slurry after the primary wet ball milling uniformly and then sending it to a spray drying tower for powdering to obtain a primary formula powder and storing it for aging for later use;

[0191] In the first-stage wet ball milling, the moisture content of the raw material entering the ball is 2.3wt%, the residue on the 200-mesh sieve is 7wt%, the material: ball: water = 1:2.5:0.36, the ball stones and ball linings used in the ball mill are all made of high-aluminum material, the ball stone grading is: Φ60mm accounts for 5wt%, Φ50mm accounts for 20wt%, Φ40mm accounts for 45wt%, Φ30mm accounts for 30wt%, and the fineness of the slurry after the first-stage ball milling is between 325-mesh sieve residue and 2.46wt%.

[0192] The spray drying tower adopts a pressure spray drying system. The spray tower uses a nozzle sheet combination with an aperture of 1.5 mm, an atomization pressure of 2.2 MPa, a drying chamber diameter greater than 10 m, a drying output of 15 t / h, and the particle gradation of the obtained powder is: the particles on the 20-mesh sieve account for 4 wt%, the particles between 20 and 40 meshes account for 36 wt%, the particles between 40 and 60 meshes account for 40 wt%, the particles between 60 and 80 meshes account for 18 wt%, and the particles below 80 meshes account for 2 wt%. The specific gravity of the powder is 0.91 g / cm 3 , the moisture content is controlled to be: 7.2wt%, and the angle of repose is controlled to be 35°.

[0193] (5.3) The obtained primary formula powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1080°C to obtain a light-burned material. In order to ensure the subsequent secondary ball milling process, the strength of the calcined light-burned material is 4.0Mpa;

[0194] (5.4) adding 3.0 wt% of white colorant (zirconium silicate), 1.5 wt% of cobalt blue colorant, 3.0 wt% of brown colorant, 5.0 wt% of encapsulated red colorant, 5.0 wt% of encapsulated yellow colorant, and 1.5 wt% of black colorant to the light-burned material, respectively, and preparing slurries of different colors by secondary wet ball milling;

[0195] The material of the secondary wet ball milling is ball: water = 1:2.5:0.38. The ball stones and ball linings used in the ball mill are all made of high-aluminum materials. The ball stone grading is: Φ8mm accounts for 10wt%, Φ4mm accounts for 30wt%, Φ3mm accounts for 40wt%, Φ2mm accounts for 20wt%, and the specific gravity of the slurry after the secondary ball milling is 1.75g / cm 3 , 40° viscosity is 68mpa.s, D50 particle size is 6.94μm;

[0196] (5.5) Load the milled slurries of different colors into the slurry decoration device.

[0197] The paste decoration device is a device that uses digital information to directly control printing. This technology can simultaneously realize the printing of 6 different color pastes, with a printing volume of 1600g per square meter.

[0198] (5.6) Inputting a preset pattern texture into the slurry decoration device, using different color slurries to carry out slurry decoration design on the surface of the ceramic body to form a delicate surface decoration layer;

[0199] The thickness of the decorative layer formed by the slurry decoration technology is between 0.85 mm;

[0200] (6) Applying slurry to the bottom of the blank in step (5);

[0201] ⑺ Firing the green body after coating the base slurry at high temperature;

[0202] ⑻ Grind the edges of the fired products directly.

[0203] Specifically, samples were prepared by the methods of Example 1, Example 2 and Example 3, respectively, and placed in a roller kiln at a temperature of 1200° C. for calcination for 60 min. After calcination, the samples were directly edged, and the wear depth, water absorption, Mohs hardness, light transmittance and surface roughness of unglazed tiles were tested according to the national standard test method for ceramic tiles or the conventional test method for ceramic tiles. The results are shown in Table 2 below:

[0204] Table 2 Performance comparison of Example 1, Example 2 and Example 3

[0205]

[0206] From the test results in Table 2, it can be seen that the samples prepared by the methods of Example 1, Example 2 and Example 3 all have good wear resistance and high Mohs hardness. The difference is that Example 1 has the best Mohs hardness and wear resistance, Example 2 forms decorative patterns with different light transmittances, and Example 3 has a lower surface roughness, and the brick surface has a delicate and comfortable texture; this is because the SiO in the slurry formula of Example 1 2 and Al 2 O 3 The content is relatively high, and corundum powder, water abrasive, zirconium silicate and other raw materials are introduced at the same time, which promotes the formation of high hardness crystal phases such as mullite, corundum, zircon, quartz, and feldspar, thereby improving the wear resistance; while the slurry formula SiO 2 The content is between 60 and 68 wt%, Al 2 O 3 The content is 15-20wt%. The formula introduces quartz powder, high potassium frit and high barium frit, and cooperates with other raw materials to promote the formation of crystals with a refractive index of about 1.50, such as barium feldspar, barium cryolite, and quartz, which are very close to the ceramic glass phase. Combined with the slurry decoration technology, a product with a light-placed decorative pattern is formed; the SiO 2 The content is between 50 and 55 wt%, Al 2 O 3 The content is 14-18wt%. The formula effectively promotes the formation of crystal phases such as calcium and celsium feldspar by introducing strontium carbonate, barium carbonate, burned talc, dolomite, high calcium frit, high barium frit, and high strontium frit, making the surface smooth and moist, forming a soft and delicate surface texture with a gloss of 10° to 20°.

[0207] Example 4

[0208] A method for preparing a digital paste-decorated ceramic tile with decorative durability comprises the following steps:

[0209] (1) drying the formed ceramic body to obtain a dried body;

[0210] (2) Spray water on the surface of the dried green body to moisten the green body;

[0211] (3) Arrange a water-based water-blocking layer on the surface of the green body wetted by water spraying;

[0212] The aqueous water-blocking layer formula is composed of the following components by weight percentage: 17wt% aqueous water-blocking agent, 2wt% emulsifier, 2wt% stabilizer, 1wt% defoamer, 76wt% free water, and 2wt% dispersant.

[0213] The water-based water-blocking layer is arranged by spray gun technology, the nozzle aperture of the spray gun is set to 0.72 mm, and the specific gravity of the water-blocking solution is set to 1.2 g / cm 3, the spraying rate is set to 15g / m 2

[0214] The water-based water-blocking agent is composed of the following raw material components by weight: 50 parts of methyl trisiloxane and 50 parts of dimethyl silicone oil;

[0215] The emulsifier is composed of the following raw material components by weight: 70 parts of sodium lauryl sulfate and 30 parts of phosphate;

[0216] The stabilizer is composed of the following raw material components by weight: 100 parts of sodium carboxymethyl cellulose;

[0217] (4) Spray water on the surface of the water-based water-blocking layer of the blank to wet the blank surface;

[0218] (5) The blank with the surface wetted by water is decorated by digital slurry decoration process according to a preset pattern to form a decorative layer;

[0219] The digital paste decoration process comprises the following steps:

[0220] (5.1) Prepare the formula materials according to the slurry formula of digital slurry decoration;

[0221] The slurry formula of the digital slurry decoration consists of the following components by weight percentage: 10wt% of corundum powder, 13.5wt% of water abrasive, 21wt% of potassium sodium stone powder, 3wt% of burned talc, 11wt% of kaolin, 13.5wt% of washed mud, 4.5wt% of bentonite, 11wt% of mixed mud, 5.5wt% of calcined aluminum vanadium, 6wt% of zirconium silicate, 0.6wt% of trimer, and 0.4wt% of defoamer.

[0222] The water-abrasive material is a raw material obtained by flotation and desulfurization of slag after primary lithium extraction, and its chemical composition is composed of the following components by weight percentage: Al 2 O 3 17.80wt%, SiO 2 69.05wt%, K 2 O 3.50wt%, Fe 2 O 3 0.87wt%, Na 2 O 3.45wt%, CaO 0.84wt%, MgO 0.42wt%, Li 2 O 0.41wt%, trace elements 0.18wt%, SO 3 0.08wt%, loss on ignition 3.40wt%; trace elements include special elements such as rubidium, gallium, strontium, cadmium, nickel, etc.

[0223] The SiO 2 Content 54.85wt%, Al 2 O 3The content is 30.55wt%, CaO content is 0.32wt%, MgO content is 1.23wt%, Fe 2 O 3 The content is 0.33wt%, K 2 O content is 2.15wt%, Na 2 O content is 1.15wt%, ZrO 2 The content is 3.92wt%, and the loss on ignition is 5.50wt%; the particle size of the corundum powder is finely ground to D50 of 2μm.

[0224] (5.2) adding water to the formula material and subjecting it to graded ball milling, wherein the graded ball milling includes primary wet ball milling and secondary wet ball milling; stirring the slurry after the primary wet ball milling uniformly and then sending it to a spray drying tower for powdering to obtain a primary formula powder and storing it for aging for later use;

[0225] In the first-stage wet ball milling, the moisture content of the raw material entering the ball is 2.3wt%, the residue on the 200-mesh sieve is 7wt%, the material: ball: water = 1:2.5:0.36, the ball stone and ball lining used in the ball mill are all made of high-aluminum material, and the ball stone grading is: Φ60mm accounts for 5wt%, Φ50mm accounts for 20wt%, Φ40mm accounts for 45wt%, Φ30mm accounts for 30wt%, and the fineness of the slurry after the first-stage ball milling is between 325-mesh sieve residue and 2.46wt%;

[0226] The spray drying tower adopts a pressure spray drying system. The spray tower uses a nozzle sheet combination with an aperture of 1.5 mm, an atomization pressure of 2.2 MPa, a drying chamber diameter greater than 10 m, a drying output of 15 t / h, and the particle gradation of the obtained powder is: the particles on the 20-mesh sieve account for 4 wt%, the particles between 20 and 40 meshes account for 36 wt%, the particles between 40 and 60 meshes account for 40 wt%, the particles between 60 and 80 meshes account for 18 wt%, and the particles below 80 meshes account for 2 wt%. The specific gravity of the powder is 0.91 g / cm 3 , the moisture content is controlled at 7.2wt%, and the angle of repose is controlled at 35°;

[0227] (5.3) The obtained primary formula powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1080°C to obtain a light-burned material. In order to ensure the subsequent secondary ball milling process, the strength of the calcined light-burned material is 4.0Mpa;

[0228] (5.4) 10wt% of white colorant (zirconium silicate), 1.5wt% of cobalt blue colorant, 3.0wt% of brown colorant, 5.0wt% of encapsulated red colorant, 4.0wt% of orange colorant, 5.0wt% of encapsulated yellow colorant and 1.5wt% of black colorant are added to the light-burned material respectively, and slurries of different colors are obtained through secondary wet ball milling.

[0229] The material of the secondary wet ball milling is ball: water = 1:2.5:0.38. The ball stones and ball linings used in the ball mill are all made of high-aluminum materials. The ball stone grading is: Φ8mm accounts for 10wt%, Φ4mm accounts for 30wt%, Φ3mm accounts for 40wt%, Φ2mm accounts for 20wt%, and the specific gravity of the slurry after the secondary ball milling is 1.75g / cm 3 , 40° viscosity is 112mpa.s, and D50 particle size is 10.42μm.

[0230] (5.5) Loading the milled slurries of different colors into the slurry decoration device;

[0231] The paste decoration device is a device that uses digital information to directly control the printing, which can realize the printing of 7 different colors of paste at the same time, with a printing volume of 1600g per square meter;

[0232] (5.6) Inputting a preset pattern texture into the slurry decoration device, using different color slurries to carry out slurry decoration design on the surface of the ceramic body to form a wear-resistant and anti-slip pattern decoration layer;

[0233] The thickness of the decorative layer formed by the slurry decoration technology is between 0.85 mm;

[0234] (6) After applying the dot pattern layer and protective glaze on the surface of the body in step (5), apply the base slurry to the bottom of the body;

[0235] The dot-spraying solution of the dot-spraying pattern layer is composed of the following components by weight percentage: 20wt% of colored dry particles, 6wt% of flash point, 55wt% of suspension, 2wt% of defoamer, 15wt% of free water, and 2wt% of dispersant;

[0236] The dot pattern layer is arranged by a dot device, the dot head of the dot device is set to a disc type, the operating frequency is set to 120 Hz, and the specific gravity of the dot solution is set to 1.35 g / cm 3 , the application rate is set to 20g / m 2 ;

[0237] The colored dry granules are composed of the following raw material components by weight: 35 parts of white dry granules, 10 parts of yellow dry granules, 15 parts of brown dry granules, 25 parts of transparent dry granules, and 15 parts of apricot dry granules;

[0238] The particle gradation of the colored dry particles is controlled such that particles on a 20-mesh sieve account for 2wt%, particles between 20 and 40 meshes account for 45wt%, particles between 40 and 60 meshes account for 30wt%, particles between 60 and 80 meshes account for 23wt%, and particles below 80 meshes account for 0wt%;

[0239] The flash point is composed of the following raw material components by weight: 15 parts of muscovite, 30 parts of phlogopite, 5 parts of biotite, 10 parts of green mica, 20 parts of iron sulfide, 5 parts of baddeleyite, 5 parts of zircon, and 10 parts of andalusite;

[0240] The particle grading of the flash point is controlled as follows: particles on the 12-mesh sieve account for 2wt%, particles between 12-20 mesh account for 40wt%, particles between 20-40 mesh account for 15wt%, particles between 40-60 mesh account for 25wt%, and particles between 60-80 mesh account for 18wt%;

[0241] ⑺The green body after coating with base slurry is fired at high temperature;

[0242] ⑻ Grind the edges of the fired ceramic products directly to finally obtain finished ceramic tiles.

[0243] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should fall within the scope of the claims of the present invention.

Claims

1. A digital paste-decorated ceramic tile with decorative durability, characterized in that: The digital slurry decoration slurry formula of the ceramic tile is composed of the following components by weight percentage: spodumene 0-6wt%, quartz powder 0-10wt%, corundum powder 0-10wt%, strontium carbonate 0-10wt%, barium carbonate 0-12wt%, potassium feldspar 0-25wt%, sodium feldspar 0-25wt%, water abrasive 0-30wt%, potassium sodium stone powder 0-40wt%, burned talc 3-8wt%, calcite 0-10wt%, dolomite 0-10wt%, kaolin 5 ~15wt%, washed mud 0~15wt%, bentonite 0~6wt%, mixed mud 0~15wt%, calcined bauxite 0~8wt%, calcined kaolin 0~10wt%, zirconium silicate 0~10wt%, high potassium frit 0~25wt%, high calcium frit 0~15wt%, high barium frit 0~10wt%, high strontium frit 0~10wt%, carboxymethyl cellulose 0~1.0wt%, trimer 0.5~1.0wt%, defoamer 0.2~1wt%.

2. The digital paste-decorated ceramic tile with decorative durability according to claim 1, characterized in that: The spodumene has a Li2O content of 4-6wt%, an Al2O3 content of 20-25wt%, and a SiO2 content of 68-78wt%.

3. The digital paste-decorated ceramic tile with decorative durability according to claim 1, characterized in that: The water-abrasive material is a raw material obtained by flotation and desulfurization of slag after lithium extraction once, and its chemical composition is as follows by weight percentage: Al2O3 15-20wt%, SiO2 65-75wt%, K2O 2-5wt%, Fe2O3 0-4wt%, Na2O 2-5wt%, CaO 0-2wt%, MgO 0-1wt%, Li2O 0.3-1wt%, trace elements ≥ 0.1wt%, SO3 0-0.2wt%, and ignition loss 0-5wt%; the trace elements include rubidium, gallium, strontium, cadmium, and nickel.

4. The digital paste-decorated ceramic tile with decorative durability according to claim 1, characterized in that: The high potassium frit has a K2O content of 13-18wt%, a Na2O content of 3-6wt%, an Al2O3 content of 17-23wt%, a SiO2 content of 53-60wt%, a CaO content of 4-8wt%, a MgO content of 0.3-0.8wt%, and a Fe2O3 content of 0.03-0.1wt%; The high calcium frit has a CaO content of 18-22wt%, an Al2O3 content of 15-26wt%, a SiO2 content of 50-60wt%, a MgO content of 2-4wt%, a Fe2O3 content of 0.01-0.1wt%, a K2O content of 2-4wt%, a Na2O content of 0.5-1.5wt%, and a ZnO content of 1-3wt%; The high-barium frit has a BaO content of 35-45wt%, an Al2O3 content of 12-18wt%, a SiO2 content of 35-45wt%, a CaO content of 2-4wt%, a MgO content of 0.2-0.5wt%, a Fe2O3 content of 0.01-0.2wt%, a K2O content of 0.2-0.5wt%, and a Na2O content of 2-5wt%; The high-strontium frit has a SrO content of 20-25wt%, an Al2O3 content of 12-20wt%, a SiO2 content of 50-55wt%, a CaO content of 3-8wt%, a MgO content of 2-6wt%, a Fe2O3 content of 0.01-0.1wt%, a K2O content of 1.5-3.0wt% and a Na2O content of 1.5-3.0wt%.

5. A method for preparing a digital paste-decorated ceramic tile with decorative durability, characterized in that: The following steps are involved: (1) drying the formed ceramic body to obtain a dried body; (2) Spray water on the surface of the dried green body to moisten the green body; (3) Arrange a water-based water-blocking layer on the surface of the green body wetted by water spraying; (4) Spray water on the surface of the water-based water-blocking layer of the blank to wet the blank surface; (5) The blank with the surface wetted by water is decorated by digital slurry decoration process according to a preset pattern to form a slurry decoration layer; (6) Applying a base slurry to the bottom of the green body in step (5) or applying a base slurry to the bottom of the green body after applying a dot pattern layer and a protective glaze to the surface of the green body in step (5); ⑺The green body after coating with base slurry is fired at high temperature; ⑻ Grind the edges of the fired ceramic products directly or polish them and then grind them to finally obtain finished ceramic tiles.

6. The method for preparing digital paste-decorated ceramic tiles with decorative durability according to claim 5, characterized in that: The water-blocking layer formulation in step (3) is composed of the following components by weight percentage: 10-20 wt% of aqueous water-blocking agent, 1-3 wt% of emulsifier, 1-3 wt% of stabilizer, 1-3 wt% of defoamer, 60-80 wt% of free water, and 1-3 wt% of dispersant; The water-based water-blocking layer is arranged by a spray gun process, the nozzle aperture of the spray gun is set to 0.5-0.8 mm, and the specific gravity of the water-blocking solution is set to 1.1-1.3 g / cm 3 , the spraying amount is set to 10-20g / m 2 ; The water-based water-blocking agent is composed of one or more of hydrogenated polysilicone oil, dimethyl silicone oil, methyl trisiloxane, ethyl trisiloxane, silane propyl ether, fluorocarbon resin, polyvinyl fluoride, epoxy resin, polyurethane, polyester, alkyd resin, acrylic acid, polyacrylic acid, polyvinyl alcohol, and polyamide; The emulsifier is composed of one or more of oleyl alcohol polyether, stearate, cetearyl glucose, methyl glucose sesquistearate, sodium stearoyl glutamate, carboxylates, sulfates, sulfonates, N-dodecyl dimethylamine, polyoxyethylene ethers, sucrose esters, polyglycerol esters, calcium stearoyl lactylate, fatty acid soaps, sodium lauryl sulfate, sodium dodecylbenzene sulfonate, phosphates, and hexaglycerol monocaprylate; The stabilizer is composed of one or more of gelatin, sodium carboxymethyl cellulose, xanthan gum, dextrin, sodium gelatinate, polysorbate 20, sodium silicate, sodium benzoate, and carrageenan.

7. The method for preparing digital paste-decorated ceramic tiles with decorative durability according to claim 5, characterized in that: The digital paste decoration process described in step (5) comprises the following steps: (5.1) Prepare the formula materials according to the slurry formula of digital slurry decoration; (5.2) adding water to the formula material and subjecting it to graded ball milling, wherein the graded ball milling includes primary wet ball milling and secondary wet ball milling; stirring the slurry after the primary wet ball milling uniformly and then sending it to a spray drying tower for powdering to obtain a primary formula powder and storing it for aging for later use; (5.3) The obtained primary formula powder is loaded into a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1050-1150°C to obtain a light-burned material. In order to ensure the subsequent secondary ball milling process, the strength of the calcined light-burned material is controlled to be <5Mpa; (5.4) Adding pigments of different colors in different proportions to the light-burned material according to the design, adding water to the light-burned material after adding the pigments to perform secondary wet ball milling to obtain slurries of different colors; (5.5) The milled slurries of different colors are loaded into a slurry decoration device; the slurry decoration device uses digital information to directly control the printing equipment, which can realize the printing of 4 to 10 different color slurries at the same time, and the printing amount per square meter is 850g to 1800g; (5.6) Input a preset pattern texture into the slurry decoration device, and use different color slurries to carry out slurry decoration design on the surface of the ceramic body to form a decorative layer with wear-resistant, anti-slip, light-transmitting, soft light, and delicate effects; the thickness of the decorative layer formed by the slurry decoration technology is between 0.5mm and 1.0mm.

8. The method for preparing digital paste-decorated ceramic tiles with decorative durability according to claim 7, characterized in that: The slurry formula of the digital slurry decoration described in step (5.1) is composed of the following components by weight percentage: spodumene 0-6wt%, quartz powder 0-10wt%, corundum powder 0-10wt%, strontium carbonate 0-10wt%, barium carbonate 0-12wt%, potassium feldspar 0-25wt%, sodium feldspar 0-25wt%, water abrasive 0-30wt%, potassium sodium stone powder 0-40wt%, burned talc 3-8wt%, calcite 0-10wt%, dolomite 0-10wt%, high Kaolin 5-15wt%, washed mud 0-15wt%, bentonite 0-6wt%, mixed mud 0-15wt%, calcined bauxite 0-8wt%, calcined kaolin 0-10wt%, zirconium silicate 0-10wt%, high potassium frit 0-25wt%, high calcium frit 0-15wt%, high barium frit 0-10wt%, high strontium frit 0-10wt%, carboxymethyl cellulose 0-1.0wt%, trimer 0.5-1.0wt%, defoamer 0.2-1wt%.

9. The method for preparing digital paste-decorated ceramic tiles with decorative durability according to claim 8, characterized in that: The spodumene has a Li2O content of 4-6wt%, an Al2O3 content of 20-25wt%, and a SiO2 content of 68-78wt%; The water-abrasive material is a raw material obtained by flotation and desulfurization of slag after lithium extraction. The chemical composition is as follows by weight percentage: Al2O3 15-20wt%, SiO2 65-75wt%, K2O 2-5wt%, Fe2O3 0-4wt%, Na2O 2-5wt%, CaO 0-2wt%, MgO 0-1wt%, Li2O 0.3-1wt%, trace elements ≥ 0.1wt%, SO3 0-0.2wt%, ignition loss 0-5wt%; the trace elements include rubidium, gallium, strontium, cadmium, and nickel; The high potassium frit has a K2O content of 13-18wt%, a Na2O content of 3-6wt%, an Al2O3 content of 17-23wt%, a SiO2 content of 53-60wt%, a CaO content of 4-8wt%, a MgO content of 0.3-0.8wt%, and a Fe2O3 content of 0.03-0.1wt%; The high calcium frit has a CaO content of 18-22wt%, an Al2O3 content of 15-26wt%, a SiO2 content of 50-60wt%, a MgO content of 2-4wt%, a Fe2O3 content of 0.01-0.1wt%, a K2O content of 2-4wt%, a Na2O content of 0.5-1.5wt%, and a ZnO content of 1-3wt%; The high-barium frit has a BaO content of 35-45wt%, an Al2O3 content of 12-18wt%, a SiO2 content of 35-45wt%, a CaO content of 2-4wt%, a MgO content of 0.2-0.5wt%, a Fe2O3 content of 0.01-0.2wt%, a K2O content of 0.2-0.5wt%, and a Na2O content of 2-5wt%; The high-strontium frit has a SrO content of 20-25wt%, an Al2O3 content of 12-20wt%, a SiO2 content of 50-55wt%, a CaO content of 3-8wt%, a MgO content of 2-6wt%, a Fe2O3 content of 0.01-0.1wt%, a K2O content of 1.5-3.0wt% and a Na2O content of 1.5-3.0wt%.

10. The method for preparing digital paste-decorated ceramic tiles with decorative durability according to claim 7, characterized in that: The first-stage wet ball milling in step (5.2) requires that the moisture content of the raw material entering the ball is ≤3wt%, the residue on the 200-mesh sieve is ≤8wt%, and the ratio of material: ball: water is 1:2.5:0.

36. The ball stones and ball linings used in the ball mill are all made of high-aluminum materials. The ball stone grading is: Φ60mm accounts for 5wt%, Φ50mm accounts for 20wt%, Φ40mm accounts for 45wt%, and Φ30mm accounts for 30wt%. The fineness of the slurry after the first-stage ball milling is 325-mesh sieve residue between 1.5 and 3.0wt%; The spray drying tower in step (5.2) adopts a pressure spray drying system, the spray tower uses a nozzle sheet combination with an aperture of 1.5mm to 2.0mm, the atomization pressure is 1.8MPa to 2.6MPa, the diameter of the drying chamber is greater than 10m, the drying output is 10-30t / h, and the particle gradation of the obtained powder is: the particles on the 20-mesh sieve account for 0-6wt%, the particles between 20-mesh and 40-mesh account for 30-40wt%, the particles between 40-mesh and 60-mesh account for 40-45wt%, the particles between 60-mesh and 80-mesh account for 15-25wt%, the particles below 80-mesh account for 0-3%, and the specific gravity of the powder is 0.85-0.95g / cm 3 , the moisture content is controlled to be: 6-8wt%, and the angle of repose is controlled to be 33°-38°; In step (5.3), colorants of different colors are added to the light-burned material, and then secondary wet ball milling is performed; the secondary wet ball milling requires that material: ball: water = 1:2.5:0.38, the ball stone and ball lining used in the ball mill are all made of high-aluminum material, and the ball stone grading is: Φ8mm accounts for 10wt%, Φ4mm accounts for 30wt%, Φ3mm accounts for 40wt%, Φ2mm accounts for 20wt%, and the slurry after secondary ball milling has a specific gravity of 1.75±0.5g / cm 3 , 40° viscosity is 60~150mpa.s, D50 particle size is 5μm~15μm; The slurries of different colors include ceramic pigments of different colors such as white, blue, brown, red, yellow, black and green; the white one is zirconium silicate.

11. The method for preparing digital paste-decorated ceramic tiles with decorative durability according to claim 5, characterized in that: Step (6) The dot pattern layer has a solution formula consisting of the following components by weight: 15-25wt% of colored dry particles, 3-6wt% of flash point, 50-60wt% of suspension, 1-3wt% of defoamer, 10-20wt% of free water, and 1-3wt% of dispersant; The dot pattern layer is arranged by a dot-spraying device, the dot-spraying device has a dot-spraying head set to a mesh or disc type, an operating frequency set to 50-200 Hz, and a dot-spraying solution with a specific gravity set to 1.2-1.4 g / cm 3 , the application rate is set to 15-25g / m 2 ; The colored dry particles are composed of one or more of white dry particles, yellow dry particles, brown dry particles, red dry particles, black dry particles, green dry particles, blue dry particles, transparent dry particles, apricot dry particles, and gray dry particles; The particle grading of the colored dry particles is controlled such that particles on a 20-mesh sieve account for 0-3wt%, particles between 20-40 mesh account for 40-50wt%, particles between 40-60 mesh account for 25-35wt%, particles between 60-80 mesh account for 20-25wt%, and particles below 80 mesh account for 0-1wt%; The flash point is composed of one or more of muscovite, phlogopite, biotite, lepidolite, sericite, green mica and iron lithium mica, hard rock mica, iron sulfide, baddeleyite, zircon, green zircon, andalusite, and kyanite; The particle grading of the flash point is controlled as follows: particles on the 12 mesh sieve account for 0-5wt%, particles between 12 mesh and 20 mesh account for 35-45wt%, particles between 20 mesh and 40 mesh account for 10-20wt%, particles between 40 mesh and 60 mesh account for 20-25wt%, particles between 60 mesh and 80 mesh account for 15-20wt%, and particles below 80 mesh account for 0-1wt%.

12. A digital paste-decorated ceramic tile with decorative durability, prepared by the preparation method according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Green brick film-forming moisturizing agent, ink-jet printing ink, decorative glue and preparation methods of green brick film-forming moisturizing agent and ink-jet printing ink

    CN110372212A

  • Dry-particle inkjet stone-like brick with whole-body effect and preparation method thereof

    CN111574228A

  • Method for preparing primary sintered microcrystalline jade by using pan jade tailing powder

    CN112521013A

  • Pattern mold texture brick with clear mold texture and preparation process thereof

    CN113526869A

  • Ceramic rock plate with multicolor light-transmitting three-dimensional effect and manufacturing method thereof

    CN113896569A